The Construction of Media in the Political Identity of Wearing Jilbab by Policewomen - Imamah, Fardan Mahmudatul (DINIKA : Academic Journal of Islamic Studies, 2016)
Veil is not only accepted as a religious obligation but also a medium of modernization and lifestyle transformation. In certain cases, it will be imposed toward becoming ‘ideology’ through various regulatory and governmental institutions. Therefore, veil is perceived as goodness and person's identity. Social conditions have changed about the veil in Indonesia. It causes a natural understanding for policewomen to also wear jilbab as well as other Muslim women, without having to be restricted by certain state regulations, including police regulations. Unfortunately, the recognition process becomes increasingly complex discourse. This paper examines three online media: kompas.com, tempo.co, and republika.co.id in the issue of the political identity of wearing jilbab by a policewoman. Using critical discourse analysis, the article shows that each of the three media has character to present the information in the certain objectification theme, in which they have an important role in influencing the policy by constructing public awareness of identity for certain goals.